Registration of 'Mela CL+' soft white winter wheat. Issue 2 (9th January 2020) - Gill, K. S.; Kumar, N.; Randhawa, H. S.; Carter, A. H.; Yenish, J.; Morris, C. F.; Baik, B.‐K; Higginbotham, R. W.; Guy, S. O.; Engle, D. A.; Chen, X. M.; Murray, T. D.; et al.
Abstract: 'Mela CL+' (Reg. no. CV‐1157, PI 675008; PVP 201500291) is a soft white common winter wheat ( Triticum aestivum L.) cultivar carrying two‐gene tolerance to imazamox herbicide, also known as Clearfield Plus, that was developed and released by the Agricultural Research Center, Washington State University, in October 2013. It was tested under the experimental designations EBC2 F3 ‐3‐20 and WA008155. Mela CL+ was developed using a marker‐assisted backcross selection method involving a cross between the soft white winter (SWW) wheat cultivar 'Eltan' and CL0618, an Australian hard red spring line carrying the two‐gene Clearfield technology. The two‐gene Clearfield technology present in Mela CL+ was due to two mutation alleles Als1 and Als2 of the acetolactate synthase ( ALS ) gene copies located on the long arm of chromosomes 6B and 6D. Mela CL+ has high grain yield potential and intermediate plant height and is well adapted to the dryland production areas of the Pacific Northwest (PNW) with <300 mm of annual precipitation. Tested in multiple locations and years, Mela CL+ showed herbicide tolerance equivalent to Clearfield Plus check cultivar 'AP503 CL2' and greater tolerance than single‐gene Clearfield cultivars grown in the PNW. Mela CL+ has end‐use quality characteristics similar to cultivars 'ORCF‐102', 'Stephens', and 'Xerpha'. As compared to Eltan, Mela CL+ has better stripe rust resistance, whereas the level of snow mold and Cephalosporium stripe tolerance is equal.